FC035: Exome Sequencing of the Israeli Dialysis-Treated Pediatric Population Reveals Monogenic Etiology in ∼44% of Cases. (3rd May 2022) - Kagan, Maayan; Ben Moshe, Yishay; Shlomovitz, Omer; Atias-Varon, Danit; Haskin, Orly; Ben-Shalom, Efrat; Magen, Daniella; Schreiber, Ruth; Volovelsky, Oded; Shasha-Lavsky, Hadas; Davidovits, Miriam; Borovitz, Yael; et al.
Abstract: BACKGROUND: Chronic kidney disease in children is estimated to be secondary to a monogenic etiology in ∼20% of patients and can arise from mutations in a multitude of different single-gene causes. Still, data are lacking on the true prevalence of genetic etiologies dates from a large scale unbiased population screen of children with advanced kidney disease. METHOD: In order to provide comprehensive real-world evidence for monogenic etiologies of childhood end-stage kidney disease—on a national level—we initiated a nation-wide multicenter study of all pediatric Israeli dialysis units. Specifically, between 2020 and 2021, we recruited ∼90% ( n = 66) of children on dialysis from all six dialysis units treating children in Israel. We conducted exome sequencing and diagnostic analysis for all patients. We assessed the diagnostic yield of genetic analysis and its relation to baseline clinical phenotypes. RESULTS: Overall, the cohort comprises 66 individuals from different families with a first-degree consanguinity rate of 47%. Participants' mean age at renal replacement therapy initiation was 8.1 years (range 1-month to 20-years). Using exome sequencing we identified a genetic etiology in 29 out of 66 (44%) participants. The most common subgroup of diagnostic variants was in genes causing renal cystic ciliopathies (e.g. NPHP1, NPHP4, PKHD1 and BBS9 ), which together explain 31% of all monogenic etiologies. This was followed by mutations in genes causing CAKUT (e.g. EYA1, HNF1B, PAX2, COL4A1 and GREB1L ), steroid-resistant nephrotic syndrome (e.g. LAGE3, NPHS1, NPHS2, LMX1B, SMARCAL1 and CRB2 ) and tubulopathies (e.g. CTNS, AQP2 ), which explain 21%, 21% and 17% of all genetic etiologies, respectively. The yield of exome sequencing was higher among non-Jewish compared with Jewish individuals (52% versus 29%) and in children from consanguineous families compared with non-consanguineous families (56% versus 31%). The final molecular diagnosis did not correspond with the pre-exome clinical diagnosis in 17% of cases. CONCLUSION: Exome sequencing in an unbiased pediatric cohort with end-stage kidney disease yields a genetic diagnosis in 44% of cases and reveals many underappreciated monogenic etiologies. Surprisingly, renal cystic ciliopathies causing-genes were more common than CAKUT genes in our cohort. These results emphasize the importance of genetic testing among children with advanced chronic kidney disease and validate the role of exome sequencing as a standard routine diagnostic tool.